Long-Term Outcomes of Cochlear Implantation in Children with Cochlear Nerve Deficiency - Mori, Anjin; Kashio, Akinori; Akamatsu, Yusuke; Ogata, Erika; Hoshi, Yujiro; Matsumoto, Yu; Iwasaki, Shinnichi; Yamasoba, Tatsuya (Archives of Clinical and Medical Case Reports, 2020)
Objective: To evaluate long-term auditory outcomes with the continuous use of cochlear implants (CIs) in pediatric patients with cochlear nerve deficiencies (CNDs). Methods: Six children with CNDs who received CIs (mean age: 38.7 months old) were retrospectively evaluated. Audiological performance was assessed with a mean follow-up of 126 months (range 63-161) using unaided and aided pure-tone average (PTA) thresholds, categories of auditory performance-II (CAP-II) scores, and the perception of Japanese monosyllabic words. CI use was evaluated by retrospective chart review. Results: Two of the six patients did not achieve sufficient PTA threshold improvement and discontinued CI use more than 7 years after implantation. The remaining four patients demonstrated improvements in PTA thresholds with CIs, while their speech understanding remained poor with CAP-II scores of 5, even in the best cases. They did not develop open-set speech perception, resulting in continued sign language use. Conclusion: The long-term auditory outcomes of CI use in CND patients are poor, and some patients may discontinue CI use. Continuous support and education in using sign language is highly recommended for children with CNDs undergoing cochlear implantation. <gdiv></gdiv>